The resistome of Aeromonas salmonicida unraveled by proteomics - Osório, Nádia Isabel Almeida (2018)
Understand the β-lactam response and resistance mechanisms in bacteria is of great value. The increasing failure to treat bacterial infections is maily due to the expression of resistance mechanisms. The aim of this study was to assess the response of Aeromonas salmonicida to β-lactams, mainly ampicillin. We focused on induced and chromosomally located β-lactamases, as well as on the general metabolic changes induced by the presence of the antibiotic, in an attempt to unveil some of the mysteries of the β-lactam “resistome” in this species. Resistance to ampicllin was induced experimentally in A. salmonicida CECT894T (AsWT), creating a derivate ampicillin resistant strain (AsR). First, we evaluated changes that occur at phenotypic level in both strains when challenged by sub inhibitory concentrations of the antibiotic. We found a decrease of growth rate, an increase in expression of inducible β-lactamases and an increase of the ability to form biofilm; these processes must be of major importance for antibiotic stress response. However, the production of virulence factors as haemolysins, proteases and toxins, showed not to be related to the antibiotic challenge but to the initial antibiotic susceptibility phenotype of each strain. Afterwards, in order to get more insights into the physiological changes upon antibiotic stress we compared subproteomes (intra and extracellular) of both strains using two-dimensional gel electrophoresis. The intracellular proteome revealed 119 proteins with changes in abundance and extracellular proteome revealed 53 proteins. Identification of these proteins and the pathways in which they are involved provided a global view of cell metabolism related to antibiotic resistance. We observed as principal changes, an increase in β-lactamase production, a decrease in membrane permeability, overexpression of efflux pumps, a decrease of cell division (growth rate reduction), shifts in metabolism (increase in proteins biosynthesis, in energy production, catabolism of carbohydrates) and an increase in oxidative stress in consequence of an adaptive response to β-lactam antibiotic. In conclusion, we found that A. salmonicida quickly responds to a β-lactam challenge, activating their intrinsic mechanisms of resistance and concurrently producing an adaptive response involving different processes, such as “persister” phenotype (reduced growth), growth in biofilm-mode, SOS response with eventual hypermutation. We also postulate the possible involvement of outer membrane vesicles as a defense mechanism. This work is the first proteomic study of antibiotic challenge in a Aeromonas spp., gaining insights into the β-lactam “resistome”. The identification of the components of this “resistome” is useful for the future development of new therapies.